DEVELOPMENT OF INTERACTIVE LEARNING MODEL BASED ON THINK PAIR SHARE TO IMPROVE STUDENT'S MATHEMATIC COMMUNICATION ABILITY - SITI Asfiranna Sari Dalimunthe; MULYONO -; EDI SYAHPUTRA (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
This study aims to: 1) determine the development of an interactive learning model based on think pair share on material (square and rectangle) that is valid, practical, and effective so that it can improve students' mathematical communication skills; and 2) describe the improvement of mathematical communication skills using an interactive learning model based on think pair share. This research is a development research. The development model used in this research is the ADDIE model. The results showed that: 1) the development of an interactive learning model based on think-paur share that was developed met the criteria of validity, practicality and effectiveness; and 2) the increase in mathematical communication skills using an interactive learning model based on think pair share increased in terms of the Ngain trial I of 0,30 with low criteria and in the second trial with moderate criteria.